Avaliação do efeito do tratamento restaurador atraumático das lesões de cárie sobre a concentração de proteínas totais e a concentração de óxido nítrico salivar - Mateus, Alanna Ramalho [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Saliva contains oxidative stress biomarkers, whose expression may be altered by the presence of caries. This study evaluated whether atraumatic restorative treatment (art) alters the concentration of total proteins and nitric oxide in the saliva of children with caries at different stages. A total of 45 children, aged 4 to 6 years, attending EMEB schools in Araçatuba, SP, were selected and divided into three groups: caries-free, enamel caries, and dentin caries. Unstimulated saliva samples were collected before, immediately after, and 21 days after clinical treatment, in which carious lesions were restored with glass ionomer cement. The collection protocol restricted the use of fluoridated products. Pre-standardized biochemical experiments were conducted to assess the concentration of total proteins and salivary nitrite (no₂⁻).. Art did not alter salivary nitrite (no₂⁻) concentration in children with caries, but increased total protein concentration, with noticeable effects 21 days after the intervention, particularly in children with dentin caries. These findings indicate that art modifies the oral environment, emphasizing the importance of integrating research, education, and clinical strategies to optimize caries prevention and control.

Saliva contains oxidative stress biomarkers, whose expression may be altered by the presence of caries. This study evaluated whether atraumatic restorative treatment (art) alters the concentration of total proteins and nitric oxide in the saliva of children with caries at different stages. A total of 45 children, aged 4 to 6 years, attending EMEB schools in Araçatuba, SP, were selected and divided into three groups: caries-free, enamel caries, and dentin caries. Unstimulated saliva samples were collected before, immediately after, and 21 days after clinical treatment, in which carious lesions were restored with glass ionomer cement. The collection protocol restricted the use of fluoridated products. Pre-standardized biochemical experiments were conducted to assess the concentration of total proteins and salivary nitrite (no₂⁻).. Art did not alter salivary nitrite (no₂⁻) concentration in children with caries, but increased total protein concentration, with noticeable effects 21 days after the intervention, particularly in children with dentin caries. These findings indicate that art modifies the oral environment, emphasizing the importance of integrating research, education, and clinical strategies to optimize caries prevention and control.
Evaluation of the effect of atraumatic restorative treatment of caries lesions on total protein concentration and salivary nitric oxide concentration
Keywords: Saliva; Cáries dentárias; Marcadores bioquímicos; Proteínas salivares; Oxido nitrico; Tratamento odontológico restaurador sem trauma; Dental caries